A Mini‐Review of E‐Waste Management in Brazil: Perspectives and Challenges. Issue 9 (17th September 2019) - de Oliveira Neto, José Francisco; Silva, Maisa Mendonça; Machado Santos, Simone
Abstract: The accelerated production and replacement of new electrical and electronic equipment demonstrates a tendency for the proportional increase in the generation of e‐waste. Developing countries experience similar social and environmental consequences from this trend, which compounds the other challenges associated with the already poor solid waste management in these regions. Moreover, the dangerous composition of some e‐waste amplifies the problems related to managing these materials. This mini‐review presents a brief overview of e‐waste management in Brazil, including technical aspects, scientific studies, and the challenges ahead. With the Brazilian National Policy of Solid Waste already in place, technical and scientific studies endorse measures that range from incorporating the informal recycling sector into the e‐waste management sector to encouraging the expansion of the recycling industry. All such actions, combined with an intensified commitment of electronic equipment manufacturers to reverse logistics, can improve e‐waste management in Brazil. Abstract : The focus of this review lies on identifying main studies related to the e‐waste theme within the scope of Brazilian technical and scientific research. The data analysis reveals that organizations of informal recycling, implementation of reverse logistics actions, and stimulation of e‐waste recycling are the main challenges to e‐waste management.